Evaluation of the MiR-513a-5p Impinges on Progesterone Receptor Protein Expression in Breast Cancer Cells: A Systematic Review and Meta-analysis - Mahrokh Koochehbaghi; Mohadeseh Khodaparasti; Afagh Jamalzadeh; Samira Jalalinezhad (International Journal of Scientific Research in Dental and Medical Sciences (IJSRDMS), 2023)
Background and aim: MicroRNAs can be considered as a predictor or cause of breast cancer.  The present study was conducted to evaluate MiR-513a-5p's impacts on progesterone receptor protein expression in breast cancer cells. Material and methods: The present study was based on the PRISMA 2020-27-item checklist.  By giving the keywords microRNAs, breast cancer, MiR-513a-5p, progesterone, all articles available in the international databases, PubMed, Web of Science, Scopus, Science Direct, Web of Knowledge, EBSCO, Wiley, ISI, Elsevier, Embase databases and Google Scholar search engine were reviewed until August 2023.  STATA/MP.  V17 software was used in this meta-analysis. Results: Three articles were included in the present study.  MiR-513a-5p upregulation was directly and statistically significantly associated with breast cancer risk (OR = 1.45; 95% CI 1.07-1.83; P<0.01). Conclusions: The results of the present study can affect different aspects of breast cancer development.  The use and identification of miR-513-a-5p as a long-term biomarker to identify the pathways involved in the early development of breast cancer should be considered.